Introduction and management of vetch/barley forage mixtures in the rainfed areas of Pakistan 3. Residual effects on following cereal crops - Qamar, I.A.; Keatinge, J.D.H.; Mohammad, N.; Ali, A.; Khan, M.A. (1999)
The residual effects of winter-sown forage mixtures grown in the northern rainfed parts of Punjab province and south-eastern North West Frontier Province in Pakistan were examined. Studies were carried out during 1994–97 primarily at the National Agricultural Research Centre (NARC), Islamabad, which has an annual rainfall of around 1000 mm and, secondarily, at a much drier site at the Arid Zone Research Centre (AZRC) at Quetta. Common vetch (V), barley (B), and their mixtures at seed ratios of V75B25, V50B50, and V25B75 were sown and 3 harvest time treatments (pre-flowering, full flowering, and maturity) were imposed. Sorghum, and then wheat, were grown as succeeding crops to monitor the residual effects of the introduction and management of legume forage mixtures. Significant residual effects on the dry matter production and nitrogen (N) content of sorghum (P < 0·01) were observed at both NARC and AZRC following different vetch/barley seed ratio treatments. Sorghum dry matter yield after pure vetch and after the mixture ratio treatment of V75B25 was higher (4·5 t/ha) than after other mixtures and it was lowest after sole barley (2·5 t/ha). The N taken up by the sorghum after pure vetch amounted to 56 kg/ha and after pure barley was 25 kg/ha. Nitrogen yield from the sorghum decreased with increasing amount of barley in the mixture. There were no apparent effects of the previous harvest time treatments imposed on the forages. Differences in dry matter production and N content in wheat following sorghum at NARC were just detectable after different vetch/barley seed ratios. The greatest amount of dry matter (>4 t/ha) with an N content of 29 kg/ha was found following pure vetch and sorghum and the lowest dry matter (3·4 t/ha) and N (23 kg/ha) following pure barley and sorghum. At AZRC, the same trends in sorghum were observed as at NARC but with reduced yields due to the substantially lower and less well distributed rainfall and suboptimal temperatures, which restricted the productivity of the initial crops in the sequence.